Usability testing of industrial training system (ITS -UTM) phase I for modules used by the students - Khoo, Song Ching, 1985-; Norazah Yusof; Fakulti Sains Komputer dan Sistem Maklumat (2009)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2009